Incorporating Value-Based Care Into Oncology. Issue 4 (July 2020) - Seymour, Erlene K.; de Souza, Jonas A.; Fendrick, A. Mark
Abstract : Abstract: Value-based care within insurance design utilizes evidence-based medicine as a means of defining high-value versus low-value diagnostics and treatments. The goals of value-based care are to shift spending and coverage toward high-value care and reduce the use of low-value practices. Within oncology, several value-based methods have been proposed and implemented. We review value-based care being used within oncology, including defining the value of oncology drugs through frameworks, clinical care pathways, alternative payment models including the Oncology Care Model, value-based insurance design, and reducing low-value care including the Choosing Wisely initiatives.